A Model Longitudinal Observation Medicine Curriculum for an Emergency Medicine Residency. (28th March 2016) - Wheatley, Matthew; Baugh, Christopher; Osborne, Anwar; Clark, Carol; Shayne, Philip; Ross, Michael
Abstract: The role of observation services for emergency department patients has increased in recent years. Driven by changing health care practices and evolving payer policies, many hospitals in the United States currently have or are developing an observation unit (OU) and emergency physicians are most often expected to manage patients in this setting. Yet, few residency programs dedicate a portion of their clinical curriculum to observation medicine. This knowledge set should be integrated into the core training curriculum of emergency physicians. Presented here is a model observation medicine longitudinal training curriculum, which can be integrated into an emergency medicine (EM) residency. It was developed by a consensus of content experts representing the observation medicine interest group and observation medicine section, respectively, from EM's two major specialty societies: the Society for Academic Emergency Medicine (SAEM) and the American College of Emergency Physicians (ACEP). The curriculum consists of didactic, clinical, and self‐directed elements. It is longitudinal, with learning objectives for each year of training, focusing initially on the basic principles of observation medicine and appropriate observation patient selection; moving to the management of various observation appropriate conditions; and then incorporating further concepts of OU management, billing, and administration. This curriculum is flexible and designed to be used in both academic and community EM training programs within the United States. Additionally, scholarly opportunities, such as elective rotations and fellowship training, are explored.